(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
A sorbent based on medioporous industrial silica by precipitated carbonizate of saccharose on it`s surface was obtained. It was shown, that obtained sorbents differ from the initial sorbents in structure of porositi, and in hidrophiliti of the surface. It has been found out, that hidrophile-hidrophob balance of its surface can be regulated by treatment of this sorbent with gas products of chemical transport reaction (CTR) ZnO/H2O2.